Application of the Social Inquiry Learning Model to Improve Elementary School Students' Social Attitude - Iswan Riyadi (Edumaspul: Jurnal Pendidikan, 2021)
With the social inquiry learning model, it is hoped that students will be able to solve problems by looking for and finding answers or solutions themselves so that in the process of solving problems, critical thinking is required to solve and find answers. The method in this research is this type of research is a queasy experimental design with a research design Nonequivalent Control Group Design. This study uses data collection techniques in the form of tests. The test given is in the form of descriptive questions to measure students' social problem-solving skills. In this case, two stages of the test passed. The first stage is the initial test (pretest), and the second is the final test (posttest). The results of this study were the normality test using the Kolmogorov-Sminov test with a significance value of 0.036 for the control class, while the significance value for the experimental type was 0.204. Because the significance value of the two categories is greater than the significance level (α) of 0.05, it can be concluded that this study is a normally distributed population. Meanwhile, the two groups' final state data normality test was based on the results after testing and normality testing using the Kolmogorov-Sminov test with a significance value of 0.190 for the control class, while a significant value for the experimental type was 0.200. Because the significance value of the two categories is greater than the significance level (α) of 0.05, it can be concluded that this study is a normally distributed population.